Chromium as a severe anthropogenic geochemical anomaly in river sediments near a tannery outfall: spatial attenuation, source apportionment and ecological risk screening - Rahat Khan; Shuvashish Das Shuvo; Md. Samium Basir; Md. Abu Bakar Siddique; Javed Mallick; Hoang Thi Hang; Md. Harunor Rashid Khan; Saad Aldawood; Dhiman Kumer Roy; Narottam Saha (Environmental Geochemistry and Health, 2026)
Relocating a polluting industry can transfer contamination to a new receiving water body rather than eliminate it, yet the resulting sediment footprint is rarely resolved beyond surface contamination. This study quantified the spatial and depth-resolved sediment footprint of relocated tannery discharge in the Dhaleshwari River, Bangladesh, and distinguished anthropogenic from geogenic elemental signatures. Sixty sediment samples from 18 sites were analysed for 15 elements by neutron activation analysis. Sites were evaluated individually and within four spatial zones (discharge, opposite riverbank, upstream, and downstream) using non-parametric statistics, sediment-quality indices, and Positive Matrix Factorisation (PMF). Chromium was the dominant anomaly, with concentrations at the discharge point reaching ~260 times the average crustal value (mean: 24,514 ± 16,058 µg/g), declining significantly with distance from the outfall and differing among zones. Depth profiles showed no significant vertical trend across the full sediment cores, but significant near-surface enrichment occurred in the near-field cores, consistent with episodic, source-proximal deposition. Half of all samples exceeded the chromium Effects Range Median threshold. Source apportionment attributed only 15.5% of elemental variance to anthropogenic, chromium-dominated inputs, compared with 65.5% to natural weathering and 19.0% to mixed natural-industrial signatures. Thus, a comparatively small anthropogenic contribution governs the sediment’s principal screening-level ecological concern. This pattern is consistent with particle-reactive Cr being rapidly retained near its release point, producing a sharply confined hotspot rather than basin-wide dispersion. Because risk estimates are based on total Cr rather than speciation or bioavailability, they do not demonstrate biological toxicity. The findings support prioritising targeted interventions at the discharge zone over basin-wide remediation for managing industrial river contamination in comparable settings.

Perfluorohexane sulfonate (PFHxS) modulates conformational transitions, ligand-binding functions and aggregation of human serum albumin - Suramya Suramya; Shivani A. Muthu; Chanchal Chauhan; Afnaan Qureshi; Sukriti Maurya; Suhel Parvez; Sheikh Raisuddin; Basir Ahmad (Environmental Toxicology and Pharmacology, 2026)

Female reproductive toxicity of chronic exposure to perfluorohexane sulfonate (PFHxS) under the confounding factor of dietary protein deficiency - Suramya Suramya; Mehjbeen Javed; Basir Ahmad; Sheikh Raisuddin (Reproductive Toxicology, 2026)

Antimicrobial Activity and Metabolic Profile of Bacteria from the Maros Pangkep Karst Region - Nur Haedar; Taswin Wijaya; Riuh Wardhani; Zaraswati D. Zainuddin; Sjafaraenan; Rustan Lebe; Djabal Nur Basir; Fuad Gani; Heri Adi (Current Microbiology, 2026)

Rising Waters: Designing Climate-Resilient Urban Drainage System - Muhammad Adnan; Fayaz Ahmad Khan; Afed Ullah Khan; Basir Ullah (Water Conservation Science and Engineering, 2026)

Environmental and Socio-economic Impacts of River Sand and Gravel Mining: A Review - Manirul Mia; Basir Ali Karikar; Sk Mohibul; Mohammad Itahdur Ali; Nazreen Khanam; Lubna Siddiqui (Environmental Management, 2026)

Influence of fuel mixture on the performance of K/Ca–Al catalyst synthesized via solution combustion method for Microwave-Assisted biodiesel Production: Optimization study via RSM - Hamed Nayebzadeh; Behgam Rahmanivahid; Basir Maleki (Fuel, 2026)

Coenzyme Q10 Modulates BDNF and it is Regulating Non-coding RNAs to Attenuate Motor Deficits and Neurodegeneration in Cerebellum of Cuprizone-Induced Demyelination Rat Model - Najmeh AminKhat; Zahra Basir; Mohammad Reza Tabandeh; Zohreh Ghotbeddin; Kaveh Khazaeel (Molecular Neurobiology, 2026)

Optimising site selection for ecosystem approaches to shrimp aquaculture in mangrove systems - Dominic Muenzel; Aji W. Anggoro; Dewi Embong Bulan; Yadi; Nurfadilah; Rahadian Pratama; Muhammad Ilman; Basir; Mariski Nirwan; Vabian Adriano; Muhammad M. Bayyan; Topik Hidayat; et al. (Aquaculture International, 2025)
Indonesia has experienced significant mangrove loss due to aquaculture expansion, particularly for shrimp farming, leading to the degradation of habitats and critical ecosystem services such as carbon storage, coastal protection, and fish spawning grounds. Ecosystem based aquaculture approaches offer a pathway to both mitigate environmental impacts and support sustainable seafood production. Here we explore the implementation of the Shrimp-Carbon Aquaculture (SECURE) approach in Berau Regency, East Kalimantan, Indonesia, which integrates mangrove restoration with organic shrimp farming to achieve sustainable aquaculture. Using environmental DNA (eDNA) metabarcoding to detect species from DNA shed into the environment, we assessed impacts of SECURE intervention compared to traditional ponds and found increased abundance of key taxonomic groups associated with healthy aquatic ecosystems, such as phytoplankton Chaetoceros, Chlorophyceae, and Cryptomonadales and zooplankton Calanoida and Cyclopoida. We then conducted a spatial prioritisation analysis to identify additional areas for SECURE implementation, considering mangrove restoration and protection potential, profitability, and intervention costs. High-priority ponds for restoration were typically set back from riverbanks, large, and spatially clustered, indicating opportunities for cost-effective, strategic expansion. This study underscores how spatial prioritisation can support strategic implementation of aquaculture to balance ecosystem-based aquaculture development with environmental conservation, offering a replicable framework for other regions facing similar challenges. This approach provides a pathway for achieving long-term sustainability in aquaculture, contributing to global food security and ecological resilience.

Optimizing LSTM for sediment load prediction in the Swat river basin, Pakistan: Evaluation of optimizers and activation functions - Nauman Gul; Afed Ullah Khan; Basir Ullah; Bakht Niaz Khan; Hamed M. Almalki; Abdulbasid S. Banga; Kailash Kumar (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Bioaccumulation of elements in the edible part of vegetables from the agricultural soil: Source apportionment and potential risks - Rahat Khan; Md Samium Basir; Narottam Saha; Kazi Anisur Rahman; Md Tazul Islam; Goshtha Gopal Biswas; Abubakr M. Idris; Md Harunor Rashid Khan; Saad Aldawood (Journal of Environmental Management, 2025)

Developmental and neurobehavioral toxicity of di-(2-ethylhexyl) phthalate (DEHP) in zebrafish larvae - Garima Jindal; Anuradha Mangla; Poonam Goswami; Mehjbeen Javed; Mohd. Anas Saifi; Iqra Mazahir; Padmshree Mudgal; Basir Ahmad; Sheikh Raisuddin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Conservation for production? The benefits of mangroves for sustainable shrimp aquaculture - Aji W. Anggoro; Miguel Castro; Muhammad Ilman; Sara Leavitt; Basir; Mariski Nirwan; Vabian Adriano; Andi Trisnawati; Topik Hidayat; Rahmadi Muis; Dzimar A. R. Prakoso; Yusuf Fajariyanto; et al. (Aquaculture International, 2025)

Mathematical validation of cleaning symbiosis between Macrobrachium lamarrei and Labeo rohita as an effective bio-control method against Argulus bengalensis - Netri Datta; Fahad Al Basir; Sagar Adhurya; Samar Kumar Saha; Santanu Ray (Ecological Modelling, 2025)

A State-of-the-Art Review of the Environmental Mixtures, Exposure, and Health Risks of PFAS: A Special Focus on Developing Countries - Amit Hasan Anik; Intehum Taufique Aurnab; Maisha Binte Sultan; Md. Samium Basir; Md. Fahim Murshed; Jannatul Mustari Jarin; Raihan Sorker; Mahbub Alam; Shafi M. Tareq (Water, Air, & Soil Pollution, 2025)

Dietary protein deficiency exacerbates perfluorohexane sulfonate (PFHxS)-induced reproductive abnormalities and metabolic disruptions in female rats - Suramya; Mehjbeen Javed; Anuradha Mangla; Suraj Kumar; Shaesta Shahid; Humaira Naaz Bhutto; Shahzad Ahmad; Basir Ahmad; Sheikh Raisuddin (Reproductive Toxicology, 2025)

Chitosan-mediated mitigation of salt stress in wheat (Triticum aestivum L.) under tissue culture conditions - Gaye Akçelik; Kamil Haliloğlu; Abdul Basir Sultani; Aras Türkoğlu; Jan Bocianowski (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)
Wheat ( Triticum aestivum L.) stands as a pivotal cereal crop and ranks among the most extensively cultivated species worldwide. It is productivity, however, is markedly hindered by both abiotic and biotic stressors, with salinity emerging as a predominant abiotic challenge in agricultural systems. Salinity is a pervasive issue in arable lands, necessitating the development of sustainable strategies to mitigate it is adverse effects while prioritizing environmental sustainability. Chitosan, a derivative of chitin, has garnered as an eco-friendly agent for alleviating salt stress due to it is biocompatibility and environmental safety. Studies have demonstrated that chitosan application can enhance plant growth parameters and bolster antioxidant defenses under saline conditions. In this study, the effects of varying chitosan concentrations (0, 1, 2, 4 mg/mL) and exposure durations (2, 4, 8 h) were investigated under different salinity levels (0, 75, 150, 225 mM) using mature embryos of the salinity-sensitive Kırik wheat variety. Key in vitro parameters assessed included the embryogenic callus formation rate (CFR), responding embryogenic callus rate (RECF), shoot formation rate (SFR) root formation rate (RFR), and the number of plants per explant (NP). The findings revealed that chitosan effectively mitigates salt stress. Notably, a 1 mg/mL chitosan concentration significantly improved CFR, RECR, and SFR, whereas a 4 mg/mL concentration was more effective for RFR and NP. The responses of RECR and CFR to salt stress exhibited similar patterns. Analysis of variance indicated that the optimal duration for a 1 mg/mL chitosan treatment was 4 h, while for the 4 mg/mL concentration, a 2-hour exposure was more effective, suggesting that shorter treatment durations are more beneficial at higher chitosan concentrations. Despite the promising results, the limited literature on the role of chitosan in tissue culture highlights the novelty of this research, emphasizing it is potential to make a unique contribution to the field. The findings of this study provide valuable insights for enhancing wheat’s resistance to salinity stress through chitosan treatment, offering practical applications in developing more resilient crop varieties.

Recycling the powder of spent alkaline batteries as a sustainable and reusable catalyst in producing biodiesel from waste cooking oil - Rauf Foroutan; Seyed Jamaleddin Peighambardoust; Mahsa Foroughi; Naeimeh Sadat Peighambardoust; Basir Maleki; Bahman Ramavandi (Environmental Research, 2025)

Unveiling the emerging concern of per- and polyfluoroalkyl substances (PFAS) and their potential impacts on estuarine ecosystems - Amit Hasan Anik; Md. Samium Basir; Maisha Binte Sultan; Mahbub Alam; Md. Mostafizur Rahman; Shafi M. Tareq (Marine Pollution Bulletin, 2025)

Sources and distribution of potentially toxic elements in urban road dust: A comparative insights and risk assessment of two polluted cities - Rahat Khan; Md. Samium Basir; Amit Hasan Anik; Sayma Zahan Akhi; Md. Harunor Rashid Khan; Sadiya Sultana; Saad Aldawood; Md. Shohel Parvez; Abubakr M. Idris; Dhiman Kumer Roy (Environmental Pollution, 2025)

Toxicokinetic and risk assessment of methylmercury in Indonesian pregnant population using physiologically-based toxicokinetic and reverse dosimetry modelling - Hasnawati Amqam; Rahayu Indriasari; Wahiduddin; Basir; Yusep Suparman (Environmental Toxicology and Pharmacology, 2025)

Betaine alleviates cerebellar endoplasmic reticulum stress and oxidative imbalance in a cuprizone model of multiple sclerosis in rat - Samaneh Rahdar; Zahra Basir; Mohammad Reza Tabandeh; Zohreh Ghotbeddin; Kaveh Khazaeel (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Selegiline Improves Cognitive Impairment in the Rat Model of Alzheimer’s Disease - Hamid Shokati Basir; Naser Mirazi; Alireza Komaki; Behnam Mohamadpour; Abdolkarim Hosseini (Molecular Neurobiology, 2025)

Robust integrated multi-mode scheduling of flexible loading and unloading operations with maintenance services in a port container terminal - Behnam Vahdani; D. Veysmoradi; M. Basir Abyaneh; M. Rashedi (Ocean & Coastal Management, 2024)

Alternating livelihoods and coping with shocks: An examination of coastal tourism in Indonesia amidst COVID-19 - Ivana Suradja; Theresia Susanti Asih; Basir; Dysi Polite Dyspriani; Hilda Lionata; Aby Marsiyono; Bambang Adhitya Nugraha; Tiara Intan Palupi; Indra Adi Putra Salam; Liliana Sierra Castillo; Asri Toldo; Andi Trisnawati; et al. (Marine Policy, 2024)

Valorization of dairy waste scum oil and rice husk ash-supported CuO nanocatalyst towards cleaner production of biodiesel: A waste-to-energy approach - Basir Maleki; Hossein Esmaeili; Yatish Kalanakoppal Venkatesh; Amruth E (Process Safety and Environmental Protection, 2024)

The Contribution of the South Asian Seas (SAS) Program to SDG 14: A Preliminary Assessment of the Targets (1–3) - Sivaji Patra; B. Dutta; Abas Basir; M. V. Ramanamurthy; T. K. Jana (Thalassas: An International Journal of Marine Sciences, 2024)

From pen and paper to digital precision: a comprehensive review of on-farm recordkeeping - Md. Samiul Basir; Dennis Buckmaster; Ankita Raturi; Yaguang Zhang (Precision Agriculture, 2024)
In the present era of agricultural digitalization, documenting on-farm operations is critical. These records contextualize other layers of data and underpin economic analysis and informed decision-making. On-farm recordkeeping is rooted in an ancient tradition and has evolved from pen and paper to digital means integrating diverse tools and methods. These tools vary widely in mode of data recording and this presents challenges in achieving complete, accurate and interoperable data. Assessing this diversity of existing recordkeeping systems is a key step toward the improvement in recordkeeping systems that enhance data quality and interoperability. Despite the importance, as of present, comprehensive studies addressing this challenge are lacking. A systematic review of existing on-farm recordkeeping systems was carried out to address their advantages and weaknesses and to analyze their features and traits, focusing on interoperability and adherence to efficient and comprehensive on-farm recordkeeping. Paper-based recordkeeping, a longstanding and reliable method, is gradually being replaced by digital platforms. Many universities and agencies have released farm management spreadsheets and interactive database forms representing the initial step toward intuitive recordkeeping. Furthermore, farm management software, web apps, and user-friendly smartphone apps are increasingly crucial for handling agricultural big data. Notably, among the surveyed software packages and apps, most of them are not free and only a few support data interoperability. The survey also indicates a scope for further development in open-source tools with automation in recordkeeping. Adopting digital on-farm recordkeeping tools can positively impact both on and off the farm, fostering data interoperability, controlled yet flexible data access, completeness, and appropriate accuracy.

Protective effects of diosmin on doxorubicin-induced testicular toxicity in rat - Alireza Malayeri; Shahin Moradi Birgani; Zahra Basir; Hadi Kalantar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Exploring the alteration of environmental radioactivity in terms of compositional elements of heavy minerals in an anthropogenically affected urban river: Radiological and ecological risks assessment - Sayma Zahan Akhi; Rahat Khan; Md. Samium Basir; Md. Ahosan Habib; Mohammad Amirul Islam; Kamrun Naher; Abubakr M. Idris; Md. Harunor Rashid Khan; Saad Aldawood; Dhiman Kumer Roy (Marine Pollution Bulletin, 2024)

Combined effect of naringin and adipose tissue-derived mesenchymal stem cell on cisplatin nephrotoxicity through Sirtuin1/Nrf-2/HO-1 signaling pathway: a promising nephroprotective candidate - Negin Amini; Fereshteh Nejaddehbashi; Mohammad Badavi; Vahid Bayati; Zahra Basir (Cell and Tissue Research, 2024)

A critical review on MOFs and COFs-based heterogeneous catalysts in biodiesel generation: Synthesis methods, structural features, mechanisms, kinetic, economic/environmental evaluation, and their performance - Basir Maleki; Hossein Esmaeili; Yatish Kalanakoppal Venkatesh; Mohammad Yusuf (Process Safety and Environmental Protection, 2024)

Preconception ethanol exposure changes anxiety, depressive and checking-like behavior and alter the expression levels of MAO-B in male offspring - Mohammad Basir Asefi; Amirhossein Heidari; Arman Hajikarim-Hamedani; Zahra Mousavi; Ghorbangol Ashabi; Mitra-Sadat Sadat-Shirazi; Mohammad-Reza Zarrindast (Neurotoxicology and Teratology, 2024)

Source specific sedimentary response towards the differential anthropogenic impacts in terms of potentially toxic elements in an urban river - Md. Samium Basir; Rahat Khan; Sayma Zahan Akhi; A.K.M. Atique Ullah; Mohammad Amirul Islam; Kamrun Naher; Abubakr M. Idris; Md. Harunor Rashid Khan; Saad Aldawood; Narottam Saha (Marine Pollution Bulletin, 2024)

Effects of ice storage on post-mortem quality changes and shelf life of Hilsa, Tenualosa ilisha (Hamilton, 1822) in Bangladesh - Bhaskar Chandra Majumdar; Angkur Chowdhury; Basir Ahammad; Md. Golam Rasul; Rakibul Hasan Md. Rabbi; Md. Hamidur Rahman; Fatematuzzahara Anny; MD Zobayer Rahman; Rasel Mia (Journal of Stored Products Research, 2024)

Zeolite 13X incorporated with Zn-Ce oxide nanocatalyst for removal of Reactive Red 120 dye: RSM-based approach - Tahereh Yarnazari; Basir Maleki; Mohsen Mansouri; Hossein Esmaeili (Environmental Monitoring and Assessment, 2024)

Improving capacitance measurements of aqueous solutions with alpha and beta corrections in a parallel-plate capacitor system: Insights into dielectric properties - Muhammad Zada; Abdul Basir; Byunghun Lee; Hyoungsuk Yoo (Journal of Food Engineering, 2024)

Impact of Cropping System and Planting Techniques On Soil Properties and Wheat Productivity Under Rainfed Condition - Ansaar Ahmed; Abdul Basir (Journal of Crop Health, 2024)

High-resolution mapping of seasonal snow cover extent in the Pamir Hindu Kush using machine learning-based integration of multi-sensor data - Abdul Basir Mahmoodzada; Pragyan Das; Divyesh Varade; Mohd Arslaan Akhtar; Sawahiko Shimada (Acta Geophysica, 2024)

Futuristic Streamflow Prediction Based on CMIP6 Scenarios Using Machine Learning Models - Basir Ullah; Muhammad Fawad; Afed Ullah Khan; Sikander Khan Mohamand; Mehran Khan; Muhammad Junaid Iqbal; Jehanzeb Khan (Water Resources Management, 2023)

The renoprotective effects of hesperidin on kidney injury induced by exposure to severe chronic dust storm particulate matter through inhibiting the Smads/TGF-β1 signaling in rat - Alireza Sarkaki; Mohammad Badavi; Fereshteh Nejaddehbashi; Somayeh Hajipour; Zahra Basir; Negin Amini (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Radiation exposure and health concerns associated with the environmental geochemistry of relatively higher radioactivity in a fresh water basin - Rahat Khan; Md. Samium Basir; Sayma Zahan Akhi; Amit Hasan Anik; Shabiha Hossain; H.M. Touhidul Islam; A.R.M. Towfiqul Islam; Abubakr M. Idris; Md. Harunor Rashid Khan; Saad Aldawood; Shafi M. Tareq (Marine Pollution Bulletin, 2023)

Marine litter management: A sustainable action plan and recommendations for the South Asian Seas region - Sivaji Patra; Muhammad Khurshid; Abas Basir; Pravakar Mishra; M.V. Ramanamurthy (Marine Policy, 2023)

Microplastics leaving a trace in mangrove sediments ever since they were first manufactured: A study from Indonesia mangroves - Muhammad Reza Cordova; Yaya Ihya Ulumuddin; Ali Arman Lubis; Muhammad Taufik Kaisupy; Singgih Prasetyo Adi Wibowo; Riyana Subandi; Deny Yogaswara; Triyoni Purbonegoro; Jeverson Renyaan; Doni Nurdiansah; Untung Sugiharto; Dienda Shintianata; et al. (Marine Pollution Bulletin, 2023)

Gentisic acid mitigates gentamicin-induced nephrotoxicity in rats - Morteza Saeedavi; Mehdi Goudarzi; Iman Fatemi; Zahra Basir; Seyyed Mohammad Ali Noori; Saeed Mehrzadi (Tissue and Cell, 2023)

A novel biomass derived activated carbon mediated AC@ZnO/NiO bifunctional nanocatalyst to produce high-quality biodiesel from dairy industry waste oil: CI engine performance and emission - Basir Maleki; Yatish Kalanakoppal Venkatesh; S. Siamak Ashraf Talesh; Hossein Esmaeili; Sakar Mohan; Geetha R. Balakrishna (Chemical Engineering Journal, 2023)

Berberine alleviates sodium arsenite-induced renal and liver toxicity by regulating oxidative stress and inflammation in rats - Mehdi Goudarzi; Mojtaba Kalantar; Alireza Malayeri; Zahra Basir; Mojtaba Haghi Karamallah; Hadi Kalantar (Toxicology and Environmental Health Sciences, 2023)

Enhanced conversion of dairy waste oil to biodiesel via novel and highly reactive UiO-66-NH2/ZnO/TiO2 nano-catalyst: Optimization, kinetic, thermodynamic and diesel engine studies - Basir Maleki; Hossein Esmaeili; Mohsen Mansouri; Dipesh Kumar; Bhaskar Singh (Fuel, 2023)

Curcumin attenuates memory impairments and long-term potentiation deficits by damping hippocampal inflammatory cytokines in lipopolysaccharide-challenged rats - Somayeh Hajipour; Sadegh Moradi Vastegani; Alireza Sarkaki; Zahra Basir; Seyedeh Parisa Navabi; Yaghoob Farbood; Seyed Esmaeil Khoshnam (Metabolic Brain Disease, 2023)

Using In Silico Bioinformatics Algorithms for the Accurate Prediction of the Impact of Spike Protein Mutations on the Pathogenicity, Stability, and Functionality of the SARS-CoV-2 Virus and Analysis of Potential Therapeutic Targets - Negin Alizadehmohajer; Shahrzad Zahedifar; Ehsan Sohrabi; Sedighe Shaddel Basir; Shima Nourigheimasi; Reza Falak; Reza Nedaeinia; Gordon A. Ferns; Asieh Emami Nejad; Mostafa Manian (Biochemical Genetics, 2023)

Monitoring land use land cover changes and its impacts on land surface temperature over Mardan and Charsadda Districts, Khyber Pakhtunkhwa (KP), Pakistan - Rehan Khan; Huan Li; Muhammad Basir; Yuan Lin Chen; Meer Muhammad Sajjad; Ihtisham Ul Haq; Barkat Ullah; Muhammad Arif; Waqas Hassan (Environmental Monitoring and Assessment, 2022)

Combined impact of predatory insects and bio-pesticide over pest population: impulsive model-based study - Fahad Al Basir; Jahangir Chowdhury; Suvendu Das; Santanu Ray (Energy, Ecology and Environment, 2022)

Pollution and contamination level of Cu, Cd, and Hg heavy metals in soil and food crop - Ramlan; M. Basir-Cyio; M. Napitupulu; T. Inoue; A. Anshary; Mahfudz; Isrun; M. Rusydi; Golar; Sulbadana; R. Bakri (International Journal of Environmental Science and Technology, 2022)
We aimed to assess and observe the accumulation of Cu, Cd, and Hg heavy metals on land and the contamination of plant tissues in Grand Forest Park, Palu, Indonesia, and its surrounding areas. The method used was a mix between survey and investigation, integrating data on research findings from before 2013 to 2016 with data from 2018. The data were analyzed using a correlation test, and descriptive statistics are presented in the form of tables and graphs. The results show that the highest concentration of Hg was found in the Poboya processing area (575.16 ppm) in 2013, though it gradually decreased to 287.64 ppm in 2018. The results of the Spearman’s rank test at the ∝ 0.05 level between average Cu land and Cu plant concentrations show that the obtained value ( r ) was 0.52 with a rho (ρ) of 0.13, which is not significant ( ρ 0.13 > 0.05), while for Cd and Hg metals, the obtained r values were 0.88 and 0.86, respectively. These two metals showed significant correlations between concentrations of Cd and Hg on land and Cd and Hg in plant tissues (both ρ 0.001 < 0.05). Specifically, the transfer factor (TF) value at the sampling sites of the Grand Forest Park area, Ngatabaru, and PBY from the average of various Hg concentrations in plants was much higher than the TF values of Cu and Cd, specifically being Hg > Cd = Cu or 0.61 > 0.17 = 0.17.

Elucidation of Mechanisms in Cu (II) Caused Hypercontraction of Rat Tracheal Rings - Farah Afrin; Seemi Farhat Basir; Luqman A. Khan (Biological Trace Element Research, 2022)

Additive Allee effect of top predator in a mathematical model of three species food chain - Supriya Mandal; Fahad Al Basir; Santanu Ray (Energy, Ecology and Environment, 2021)

Liver functions in combined models of the gentamicin induced nephrotoxicity and metabolic syndrome induced by high fat or fructose diets: a comparative study - Zaid O. Ibraheem; Sinan Subhi Farhan; Ajwad Al Sumaidaee; Layth Al sufi; Anas Bashir; Anmar Balwa; Rusliza Basir (Toxicological Research, 2021)

Cobalt-Induced Hypercontraction is Mediated by Generationof Reactive Oxygen Species and Influx of Calcium in Isolated RatAorta - Shahnawaz Ahmad Wani; Luqman Ahmad Khan; Seemi Farhat Basir (Biological Trace Element Research, 2020)

Study on enzyme inhibition in biodiesel synthesis: effect of stepwise addition of methanol and removal of glycerol - Fahad Al Basir; Priti Kumar Roy (Energy, Ecology and Environment, 2019)

Effects of Restoring the Primary Dentition with Stainless-Steel Crowns on Children’s Salivary Nickel and Chromium Levels, and the Associations with Saliva pH: a Preliminary Before-After Clinical Trial - Leila Basir; Razieh Meshki; Azam Behbudi; Vahid Rakhshan (Biological Trace Element Research, 2019)

Dissecting the genetic architecture of waterlogging stress-related traits uncovers a key waterlogging tolerance gene in maize - Feng Yu; Kun Liang; Zuxin Zhang; Dengxiang Du; Xuehai Zhang; Hailiang Zhao; Basir UI haq; Fazhan Qiu (Theoretical and Applied Genetics, 2018)

Delta-9-Tetrahydrocannabinol (∆9-THC) Induce Neurogenesis and Improve Cognitive Performances of Male Sprague Dawley Rats - Noor Azuin Suliman; Che Norma Mat Taib; Mohamad Aris Mohd Moklas; Rusliza Basir (Neurotoxicity Research, 2018)

A model for the control of the mosaic virus disease in Jatropha curcas plantations - Ezio Venturino; Priti Kumar Roy; Fahad Al Basir; Abhirup Datta (Energy, Ecology and Environment, 2016)

Effects of 2-amino-8-hydroxyquinoline interaction on the conformation of physiological isomers of human serum albumin - Sonali M. Shiriskar; Neeraj Agarwal; Raghuvir R. S. Pissurlenkar; Basir Ahmad (European Biophysics Journal, 2015)

Modulation of Pb(II) Caused Aortal Constriction by Eugenol and Carvacrol - Hiba Shabir; Swati Kundu; Seemi Farhat Basir; Luqman A. Khan (Biological Trace Element Research, 2014)

Effect of Lower Doses of Vanadate in Combination with Azadirachta indica Leaf Extract on Hepatic and Renal Antioxidant Enzymes in Streptozotocin-Induced Diabetic Rats - Jaya Upreti; Shakir Ali; Seemi Farhat Basir (Biological Trace Element Research, 2013)

Carbonaceous species in total suspended particulate matters at different urban and suburban locations in the Greater Dhaka region, Bangladesh - Abdus Salam; Md. Basir Ullah; Md. Safiqul Islam; Md. Abdus Salam; Shah M. Ullah (Air Quality, Atmosphere & Health, 2013)

Prevalence of GJB2 (CX26) gene mutations in south Iranian patients with autosomal recessive nonsyndromic sensorineural hearing loss - Seyed Basir Hashemi; Mohamad Javad Ashraf; Mohamad Saboori; Negar Azarpira; Masumeh Darai (Molecular Biology Reports, 2012)

Identification of Fibrinogen-Binding Proteins of Aspergillus fumigatus Using Proteomic Approach - Santosh Kumar Upadhyay; Poonam Gautam; Hrishikesh Pandit; Yogendra Singh; Seemi Farhat Basir; Taruna Madan (Mycopathologia, 2012)

Association analysis of p16 (CDKN2A) and RB1 polymorphisms with susceptibility to cervical cancer in Indian population - Nisha Thakur; Showket Hussain; Vilas Nasare; Bhudev C. Das; Seemi Farhat Basir; Mausumi Bharadwaj (Molecular Biology Reports, 2012)

Transcriptomic and Proteomic Profile of Aspergillus fumigatus on Exposure to Artemisinin - Poonam Gautam; Santosh Kumar Upadhyay; Wazid Hassan; Taruna Madan; Ravi Sirdeshmukh; Curam Sreenivasacharlu Sundaram; Wasudev Namdeo Gade; Seemi Farhat Basir; Yogendra Singh; Puranam Usha Sarma (Mycopathologia, 2011)

Antifungal activity of α-methyl trans cinnamaldehyde, its ligand and metal complexes: promising growth and ergosterol inhibitors - Sheikh Shreaz; Rayees A. Sheikh; Rimple Bhatia; Khan Neelofar; Sheikh Imran; Athar A. Hashmi; Nikhat Manzoor; Seemi F. Basir; Luqman A. Khan (BioMetals, 2011)

Allergens/Antigens, Toxins and Polyketides of Important Aspergillus Species - Preetida J. Bhetariya; Taruna Madan; Seemi Farhat Basir; Anupam Varma; Sarma P. Usha (Indian Journal of Clinical Biochemistry, 2011)

Aberrant promoter methylation and reduced expression of p16 gene in esophageal squamous cell carcinoma from Kashmir valley: a high-risk area - Irfana Salam; Showket Hussain; Mohammad Muzaffar Mir; Nazir Ahmad Dar; Safiya Abdullah; Mushtaq Ahmad Siddiqi; Riyaz Ahmad Lone; Showkat Ahmad Zargar; Shashi Sharma; Suresh Hedau; Seemi Farhat Basir; Alok Chandra Bharti; et al. (Molecular and Cellular Biochemistry, 2009)

Expressed sequence tags of Aspergillus fumigatus: Extension of catalogue and their evaluation as putative drug targets and/or diagnostic markers - Santosh Kumar Upadhyay; Jata Shankar; Yogendra Singh; Seemi Farhat Basir; Taruna Madan; P. Usha Sarma (Indian Journal of Clinical Biochemistry, 2009)

Evaluation of the anti-pyretic potential of Orthosiphon stamineus Benth standardized extract - M. F. Yam; L. F. Ang; R. Basir; I. M. Salman; O. Z. Ameer; M. Z. Asmawi (Inflammopharmacology, 2009)

Formation of a molten globule like state in bovine serum albumin at alkaline pH - Priyankar Sen; Basir Ahmad; Rizwan Hasan Khan (European Biophysics Journal, 2008)

Effect of Hormone Replacement Therapy in Normalizing Age Related Neuronal Markers in Different Age Groups of Naturally Menopausal Rats - K. Moorthy; Umesh C. S. Yadav; M. R. Siddiqui; Anil K. Mantha; Seemi F. Basir; D. Sharma; Sudha M. Cowsik; Najma Z. Baquer (Biogerontology, 2005)

Amelioration of altered antioxidant status and membrane linked functions by vanadium andTrigonella in alloxan diabetic rat brains - Mohammad Rizwan Siddiqui; Asia Taha; K. Moorthy; Mohd. Ejaz Hussain; S. F. Basir; Najma Zaheer Baquer (Journal of Biosciences, 2005)

Identification and characterization of polyubiquitin gene from cDNA library of aspergillus fumigatus - Jata Shankar; Taruna Madan; Seemi Farhat Basir; P. Usha Sarma (Indian Journal of Clinical Biochemistry, 2005)

Effect of Estradiol and Progesterone Treatment on Carbohydrate Metabolizing Enzymes in Tissues of Aging Female Rats - K. Moorthy; Umesh C.S. Yadav; M.R. Siddiqui; D. Sharma; S.F. Basir; N.Z. Baquer (Biogerontology, 2004)

Estradiol and progesterone treatments change the lipid profile in naturally menopausal rats from different age groups - K. Moorthy; Umesh C. S. Yadav; Anil K Mantha; Sudha M. Cowsik; D. Sharma; S. F. Basir; N. Z. Baquer (Biogerontology, 2004)